Raising Spiritual and Educational Work To A New Level In Uzbekistan, Studying The State Of The Socio-Spiritual Environment, and Technologies For Its Improvement - qizi, Turobova Zulfizar Ulug’bek (Buletin Antropologi Indonesia, 2024)
This article analyzes the technologies for elevating spiritual and educational activities in Uzbekistan to a new level, studying and improving the socio-spiritual environment. It examines the composition of the social environment, the spirituality of youth, problems in the education system, and the role of mass media. Methods for solving existing problems through innovative approaches, educational programs, and modern technologies are proposed. The article emphasizes the necessity of joint efforts by the state and the public in enhancing social values and provides practical recommendations aimed at educating future generations.